1994
DOI: 10.1002/ajmg.1320490204
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of trisomy 18 and trisomy 13: I. Growth, physical assessment, medical histories, survival, and recurrence risk

Abstract: The natural history of trisomy 18 and trisomy 13 was investigated using data derived from parent questionnaires and medical records from 98 families with an index case of trisomy 18 and 32 families with an index case of trisomy 13. Data are presented on pregnancy, delivery, survival, medical complications, immunizations, growth, cause of death, cytogenetics, and recurrence risk. Half of the trisomy 18 babies were delivered by C-section. Fetal distress was a factor in half, and the only reason in a third of C-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

35
224
5
14

Year Published

1996
1996
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(281 citation statements)
references
References 60 publications
(50 reference statements)
35
224
5
14
Order By: Relevance
“…Another populationbased study by Rasmussen et al [2003] showed that the presence of a congenital heart defect did not seem to affect survival. A support group-based study by Baty et al [1994] showed the major cause of death as cardiopulmonary arrest. The review by Carey, [2001] mentioned that central apnea, or its presence with a combination of other factors, was the primary pathogenesis of the increased infant mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another populationbased study by Rasmussen et al [2003] showed that the presence of a congenital heart defect did not seem to affect survival. A support group-based study by Baty et al [1994] showed the major cause of death as cardiopulmonary arrest. The review by Carey, [2001] mentioned that central apnea, or its presence with a combination of other factors, was the primary pathogenesis of the increased infant mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The ligation surgery improved heart failure and enabled the patient to be discharged and prolonged survival (553 days). To date, several case reports described five patients who underwent seven cardiac surgeries [Van Dyke and Allen, 1990;Baty et al, 1994;Teraguchi et al, 1997;Derbent et al, 2001]. Research by the Support Organization for Trisomy 18, 13 and Related Disorders (SOFT) Registry group found that eight of twelve patients who underwent cardiac surgery (seven intracardiac repairs and five palliative) survived to be discharged [Carey, 2001].…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] The condition leads to many different developmental problems such as growth deficiency, feeding and breathing difficulties, developmental delays, and psychomotor mental retardation. 5 Recent studies document that 50% of liveborn infants with trisomy 18 survive beyond the first week of life, 1 with 5 to 10% surviving beyond the first year.…”
Section: Introductionmentioning
confidence: 99%
“…31 Mosaicism is most commonly found for chromosome 18 and these known mosaics have variable phenotypes from normal intellect to severe malformations. 32 The analysis of tissue-specific mosaicism is very difficult in living cohorts. Using interphase FISH on tissue samples from a deceased neonate with unexplained abnormalities, a 17% trisomy 18 line was found in liver but was not in lymphocytes, fibroblasts or kidney.…”
Section: Discussionmentioning
confidence: 99%